Improvement of Student Teams' Progress in Project-Based Learning - Furumoto, Masahiro; Okano, Yoshinobu; Takenaka, Hideki; Sahara, Hironori; Oshima, Sota (Journal of Learning Analytics, 2022)
PBL-type classes have been widely introduced as a method of team education, but sometimes the team goes astray, and both the implementer and the participants end up not being able to feel the effects of PBL. For the two years of the "Research Project Exercise (4)" offered by the university, an activation and evaluation of the project activities by the teams were analyzed using the indicators of working hours, deviation from a certain progress, and margin of team. As a result, the introduction of reviewing the previous year's final report and the holding of multiple debriefing sessions resulted in a smoother project start and increased working hours. We also introduced the Gini coefficient as an index to evaluate team activation, and applied it to the working hours of the team and the members in the first and second years. The results showed that the working hours was closer to equal distribution in the second year than in the first year, and the variation in teams' and members' working hours was significantly reduced. The method described in this paper can be used to evaluate the activation of teams and team members, to quantitatively identify teams and team members that are not showing significant activation, and to determine the need for leveraging.